Antibiotic Resistance in Domestic Wastewater: Addressing Treatment Inefficiencies and the Imperative for Sanitation System Enhancement - Sofiyah, Evi Siti; Ridhosari, Betanti; Zahra, Nurulbaiti Listyendah; Sastroredjo, Suharti (Journal of Sustainable Infrastructure, 2024)
The increasing detection of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in domestic wastewater represents a pressing global environmental and public health challenge. Wastewater treatment plants (WWTPs), while designed to remove conventional pollutants, are increasingly recognized as reservoirs and hotspots for the persistence and horizontal gene transfer (HGT) of ARGs among microbial communities. This study aims to explore the mechanisms underlying bacterial antibiotic resistance, evaluate the limitations of conventional treatment processes –particularly disinfection methods such as chlorination – in effectively removing ARB and ARGs, and assess the implications for sanitation management in Indonesia. A systematic literature review (mini-review format) was conducted to synthesize recent findings on ARB/ARGs presence in WWTPs and the performance of existing treatment technologies. Results show that ARGs can persist even after disinfection, especially in extracellular forms, and that chlorination may, in some cases, promote ARGs release through cell lysis. Furthermore, several resistant strains demonstrate tolerance to standard chlorine doses. In Indonesia, where domestic wastewater treatment coverage and compliance remain inadequate, the uncontrolled discharge of partially treated or untreated wastewater exacerbates the spread of antibiotic resistance in aquatic environments. This study concludes that existing treatment systems are insufficient to address antibiotic resistance risks and emphasizes the urgent need for improved sanitation infrastructure, monitoring, and targeted treatment technologies.